2022
DOI: 10.3389/fpsyg.2022.1019561
|View full text |Cite
|
Sign up to set email alerts
|

English as a foreign language learners’ strategy awareness across proficiency levels from the perspective of self-regulated learning metafactors

Abstract: The previous three decades have seen a growing body of research into language learners’ self-regulated learning (SRL), language learning strategy (LLS) use, and their possible effects on proficiency. This study thus provides insights into the relationship between elementary and low intermediate learners’ perceptions of their self-regulated strategy use in English as a foreign language (EFL) and their attitude to English in relation to their proficiency level. Nine hundred and sixty-six higher proficiency stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The other plausible explanation for this finding is that because low-skilled writers frequently rely on their emotions, they tend to use affective tactics like relaxing more frequently. The results of the research conducted by Habók et al (2022) confirm this finding. They found that low-proficiency language learners most frequently used affective and motivational techniques.…”
Section: The Frequent Use Of Affective Strategiessupporting
confidence: 69%
“…The other plausible explanation for this finding is that because low-skilled writers frequently rely on their emotions, they tend to use affective tactics like relaxing more frequently. The results of the research conducted by Habók et al (2022) confirm this finding. They found that low-proficiency language learners most frequently used affective and motivational techniques.…”
Section: The Frequent Use Of Affective Strategiessupporting
confidence: 69%
“…Some researchers (Hosseinpur & Kazemi, 2022) identified that high proficiency students use more strategies and the students with poor writing skills have the knowledge of strategy use. However, their knowledge does not coincide with the implementation part while writing (Habók et al, 2022;Teng, 2022). Therefore, the findings conclusively affirm that these students must engage in active implementation of the strategies during communication, regardless of their awareness of the strategies (Damanik, 2022;Li, 2022;Zhang & Goh, 2006).…”
Section: Review Of Literaturementioning
confidence: 71%
“…The aim of this research is to investigate the self-regulated learning strategies employed by Vietnamese English as a Foreign Language (EFL) students and to explore any potential causal link between selfregulated language learning and the language pro ciency of learners. In recent years, there has been a surge in captivating studies focusing on the basis, nature, and advancement of learners' capacity to selfregulate their learning, aiming to facilitate the learning process (Alotaibi, 2017;Fukuda, 2018;Habók & Magyar, 2018;Habók et al, 2022;Kim et al, 2015;Lin, 2019). However, there are not many studies that investigated self-regulated learning strategies and the correlation between self-regulation and language pro ciency among undergraduate language learners, especially in EFL settings in the Vietnamese context.…”
Section: Introductionmentioning
confidence: 99%